Perbandingan proses penurunan kromium heksavalen oleh ferus sulfat dalam medium berasid dan beralkali - Siti Rozaimah Sheikh Abdullah,; Lau , Ming Ngo; Saleha Atan, (2004)
Reduction process followed by precipitation is the most common method used in treating wastewater containing chromium ions. In this study, hexavalent chromium reduction process was carried out in both acidic and alkaline mediums. Ferrous sulphate solution was used as a reducing agent to reduce hexavalent chromium (Cr6+) to trivalent chromium (Cr3+). The reaction in alkaline medium at pH 9.0 was achieved by adding sodium hydroxide solution (NaOH) since chromium wastewater was acidic. During the reaction, the addition of ferrous sulphate solution into reaction medium was monitored through oxidation-reduction potential (ORP) parameter. The results showed that the ORP profiles for the reduction process were different in both acidic and alkaline mediums. When the reduction process was completed in the acidic medium, the absolute ORP value was recorded as 380 mV. The absolute ORP value when the reduction process completed in the alkaline medium was in the range of 0 to –300 mV. The total precipitation in the alkaline medium was 1.6 times higher than acidic medium. For the reduction process in both acidic and alkaline mediums, the rate of reduction process was faster for the higher concentration of Cr6+ion. However, the rate of reduction process in the acidic medium was faster than the alkaline medium because the reduction of Cr6+ concentration was greater in the acidic medium